Networks of social movements in quilombola community of Salvaterra, Marajó, Pará: Redes de movimentos sociais em comunidade quilombola de Salvaterra, Marajó, Pará - de Souza Lages, Lara Thaís; Cardoso e Cardoso, Luis Fernando; Schmitz, Heribert (Programa de Pós-graduação em Desenvolvimento, Agricultura e Sociedade da Universidade Federal Rural do Rio de Janeiro (CPDA/UFRRJ), 2019)
We analyze how the quilombola movements of Salvaterra articulate themselvesthrough networking, both internally and externally, to access socio-territorial rights. To trace the network, we depart from the Quilombola community of Pau Furado, in the municipality of Salvaterra, on the Island of Marajó (PA), to Malungu, a statewide organization that joins the quilombola associations of the state of Pará. The investigation relied on the theoretical works of Alberto Melucci and Ilse Scherer-Warren. The field research, carried out in the Pau Furado community, used direct observations and interviews. The results show the strengthening of the institutionalities of the Quilombola social movements to claim their rights before governmental agencies, at the local, state and national levels.Keywords: social movements; fight for rights; networks; quilombola communities; Marajó Island.LAGES, Lara Thaís de Souza; CARDOSO, Luis Fernando Cardoso e; SCHMITZ, Heribert. Redes de movimentos sociais em comunidade quilombola de Salvaterra, Marajó, Pará. Estudos Sociedade e Agricultura, v. 27, n. 2, p. 328-351, jun. 2019.Submitted in march 2019.Accepted in may 2019.